Public-Private Partnership in the Healthcare and Pharmaceutical Sectors of Kazakhstan: Problems and Solutions - ISSATAYEVA, Nurlyaiim T.; DATKHAYEV, Ubaidilla M.; ZHAKIPBEKOV, Kairat S.; SERIKBAYEVA, Elmira A.; UMIRZAKHOVA, Galiya Zh. (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).22, 2020)
Public-private partnership is one of the main ways to solve the social problems of modern states. In Kazakhstan, the main strategic direction of the development of the healthcare system is the modernization of existing medical organizations and the construction of new healthcare facilities. The purpose of the paper was to investigate the theory and practice of public-private partnership (PPP) in the healthcare and pharmaceutical sectors, to identify the main issues and find their solutions. The leading research method was the analysis and synthesis method, which enabled the characterization of attributes and principles of PPPs, allowed to classify, and consider the most striking examples. Considering the differences between PPP contracts, we addressed not only the functions and content of such contracts, but also the terms, and the risks involved. The advantages for each of the interested parties in PPP were analyzed: private sector, public sector, consumers. The analysis of the current state of PPPs in the field of interest in Kazakhstan was performed. The generalization of world experience and the analysis of best practices allowed to develop action-oriented proposals for the further development of PPPs in Kazakhstan’s healthcare, including those that concern attraction of foreign companies with regard to the issue of concessions in the field of medical and pharmaceutical infrastructure.